Cell mediated therapeutics for cancer treatment: tumor homing cells as therapeutic delivery vehicles - Balivada, Sivasai (Kansas State University, 2013)
Many cell types were known to have migratory properties towards tumors and different research groups have shown reliable results regarding cells as delivery vehicles of therapeutics for targeted cancer treatment. Present report discusses proof of concept for 1. Cell mediated delivery of Magnetic nanoparticles (MNPs) and targeted Magnetic hyperthermia (MHT) as a cancer treatment by using in vivo mouse cancer models, 2. Cells surface engineering with chimeric proteins for targeted cancer treatment by using in vitro models. 1. Tumor homing cells can carry MNPs specifically to the tumor site and tumor burden will decrease after alternating magnetic field (AMF) exposure. To test this hypothesis, first we loaded Fe/Fe3O4 bi-magnetic NPs into neural progenitor cells (NPCs), which were previously shown to migrate towards melanoma tumors. We observed that NPCs loaded with MNPs travel to subcutaneous melanoma tumors. After alternating magnetic field (AMF) exposure, the targeted delivery of MNPs by the NPCs resulted in a mild decrease in tumor size (Chapter-2). Monocytes/macrophages (Mo/Ma) are known to infiltrate tumor sites, and also have phagocytic activity which can increase their uptake of MNPs. To test Mo/Ma-mediated MHT we transplanted Mo/Ma loaded with MNPs into a mouse model of pancreatic peritoneal carcinomatosis. We observed that MNP-loaded Mo/Ma infiltrated pancreatic tumors and, after AMF treatment, significantly prolonged the lives of mice bearing disseminated intraperitoneal pancreatic tumors (Chapter-3). 2. Targeted cancer treatment could be achieved by engineering tumor homing cell surfaces with tumor proteases cleavable, cancer cell specific recombinant therapeutic proteins. To test this, Urokinase and Calpain (tumor specific proteases) cleavable; prostate cancer cell (CaP) specific (CaP1 targeting peptide); apoptosis inducible (Caspase3 V266ED3)- rCasp3V266ED3 chimeric protein was designed in silico. Hypothesized membrane anchored chimeric protein (rCasp3V266ED3, rMcherry red) plasmids were constructed. Membrane anchoring and activity of designed proteins were analyzed in RAW264.7 Mo/Ma and HEK293 cells in vitro. Further, Urokinase (uPA) mediated cleavage and release of rCasp3V266ED3 from engineered cells was tested (Chapter-4). Animal models for cancer therapy are invaluable for preclinical testing of potential cancer treatments. Final chapter of present report shows evidence for immune-deficient line of pigs as a model for human cancers (Chapter-5)
Keywords: Cancer therapy; Cell mediated Magnetic hyperthermia; Magnetic nanoparticles; Cells as delivery vehicles; cell engineering; Immunodeficient porcine model; Magnetic hyperthermia; Medicine (0564)